Sustainable Planning for Health – Review of Frameworks for Health System Strengthening. (20th October 2021) - Rasch, L; Quentin, W; Geene, R
Abstract: Background: Imbalances in the distribution of health as well as global interconnectedness led to the consideration of health as a global public good. Health is placed therefor at the center of the goal-based movement for sustainability led by the United Nations (UN). Health System Strengthening (HSS) is an approach to align and harmonize all stakeholders in sustainable planning for health. Methods: Frameworks published by nation states, multilateral institutions or global health initiatives were retrieved and analyzed in form of a critical realist review informed by poststructuralist curiosity. The aim was to understand how these frameworks contribute to the context of sustainable planning for health with the overall goal of improved health system performance. Results: Eleven frameworks published by nation states, multilateral institutions or global health initiatives were obtained for this thesis. The frameworks support an understanding of how a health system is structured, how resources are allocated, how the financing and delivery of care is organized and how the different stakeholders of a health system are governed. Frameworks for health systems are a policy tool to introduce a common language for the architecture of health systems and to describe the way in which performance relates to functions in the form of a result-chain. The stakeholders involved in the development and implementation of these approaches are limited and predominantly from the global south. Gender, Equity and Human-rights criteria (GER-criteria) to address values are not sufficiently reflected in the frameworks. Conclusions: The analysis in this thesis shows that HSS is an approach that requires an understanding of health system architecture and how it relates to performance. Although the different frameworks make the case for performance assessment and the linkage to resources, what is missing is a value-based approach that centers the knowledge generated by the Global South. Key messages: Frameworks for HSS are policy tools for a common language for the architecture of health systems and to describe the way in which performance relates to functions in the form of a result-chain. Value-based approaches that center the knowledge generated by the Global South need to be included in sustainable planning for health.